Fuzzy databases modeling, design, and implementation - Galindo, Jose 1970- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2006)
"This book includes an introduction to fuzzy logic, fuzzy databases and an overview of the state of the art in fuzzy modeling in databases. It proposes also a method to translate FuzzyEER model to a classical DBMS, and defines FSQL (Fuzzy SQL), an extension of the SQL language that allows users to write flexible conditions in queries, using all extensions defined by the FuzzyEER model. "--Provided by publisher